Ergasilus turucuyussp. n. (COPEPODA: ERGASILIDAE) DAS BRÂNQUIAS DE Acestrorhynchus falcatus(BLOCH, 1794) E A. falcirostris(CUVIER, 1819) (CHARACIFORMES: CHARACIDAE) DA AMAZÔNIA BRASILEIRA - Malta, Jose Celso de Oliveira; Varella, Angela Maria Bezerra (Acta Amazonica, 1996)
Ergasilus turucuyussp. n. (Copepoda, Poecilostomatoida, Ergasiiidae) is proposed. The specimens were collected from the gill filaments of the freshwater fishes Acestrorhynchus falcatusand A. falcirostrisfrom Pacaás Novos River, Rondônia state, Brazil. The new species has a falciform pectinate seta on the first exopod that indicates relationship to five previously described Amazonian species. This species differs from others in the ornamentation of the legs, antenna, abdominal somites and by having a wider cephalosome.
Ergasilus turucuyussp. n. (COPEPODA: ERGASILIDAE) from the gills of Acestrorhynchus falcatus(BLOCH, 1794) e A. falcirostris(CUVIER, 1819) (CHARACIFORMES: CHARACIDAE) from Brazilian Amazon
Keywords: Copepoda; Ergasilus Turucuyus; Fish Parasites; Amazon; Copepoda; Ergasilus Turucuyus; Parasita De Peixes; Amazônia